Effects of salinity on ion accumulation in maize (Zea mays L. cv. Bari-7) (Bangladesh Journal of Botany, 2008)
NaCl salinity in the range of 50 to 200 mM increased Na+ accumulation in the root and shoot of 7-, 14- and 21-day-old maize seedlings. The accumulation of Na+ and Cl- increased but K+ accumulation decreased with the increase in NaCl concentration from 50 to 200 mM in the root and shoot of maize in all the three ages. Key words: Salinity, NaCl, Ion transport, Root, Shoot, Maize doi:10.3329/bjb.v37i2.1733 Bangladesh J. Bot. 37(2): 203-205, 2008 (December)